Visualization construction algorithm of micro-course system based on mobile network. (3rd October 2017) - Kang, Yingjian; Ma, Lei; Gong, Gecui
Abstract: Aiming at the problem that the module in the visualization of micro-course resources has slow decomposing rate and poor mapping, a new visualization construction algorithm for micro-course system is proposed. The algorithm is based on the linear limit histogram to decompose the characteristics of the micro-course system module. The decomposed modules are fused and mapped with the hue mapping algorithm to complete the micro-course system visualization construction research. The experimental results show that the algorithm can comprehensively understand the structure of the course, effectively solve the problem of slow running and poor mapping effect, and its feasibility is high.